Synergistic effect of CPPU and benzyladenine on embryo rescue in six. stenospermocarpic cultivars of grapevine - Nookaraju, A.; Barreto, M. S.; Karibasappa, G. S.; Agrawal, Dinesh C. (Vitis, 2007)
In ovulo/embryo culture technique has been used to recover hybrids from seedless grapevines. The present investigation was carried out to study the influence of pre-bloom sprays of N-(2-chloro-4-pyridyl)-N'-phenylurea (CPPU) - a synthetic cytokinin, and N-6-benzyladenine (BA) supplemented in culture media on embryo recovery in six stenospermocarpic grapevine cultivars. The results showed synergistic effect of CPPU and BA on embryo recovery. Though a CPPU spray alone increased embryo recovery in four out of six cultivars tested, the efficiency was enhanced several fold on culture of excised ovules on media supplemented with BA. The percentage of embryo recovery also depended on BA concentration and varied among six cultivars indicating a genotypic influence as well. Germination percentage of rescued embryos varied among the six cultivars and mostly corresponded with embryo recovery. Germinated embryos developed into normal plantlets. Present study demonstrates that spraying of panicles with CPPU and incorporation of BA in the ovule culture medium can enhance the embryo recovery in stenospermocarpic cultivars of grapevine.
Keywords: benzyladenine; CPPU; embryo rescue; seedless grapes